Femmes, attitudes performatives: aux lisières de la performance et de la danse - Colloque "Femmes, aux lisières de la performance et de la danse" (2012 : Vandœuvre-lès-Nancy, France), attitudes performatives; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy (Les Presses du réel, 2014)
La place et le rôle des femmes dans l'art et dans le spectacle vivant, entre 1912 et 2012, aux lisières de la performance et de la danse. A l'heure des re-enactements et autres remakes des performances historiques, il semblait important de s'interroger sur la place des femmes dans les avant-gardes des années 1910-1970. Quel regard portons-nous, aujourd'hui, sur les pionnières qui ont profondément modifié la danse et la performance, en Europe et aux Etats-Unis ? Réunis pour la première fois, des historiens, des philosophes, des danseurs et deux chorégraphes ont accepté de faire le point sur leurs recherches. Par-delà les catégories artistiques (danse, performance, action, pantomime, théâtre, music-hall...) et les clivages (théorie / pratique ; forme / fond), ce livre est une invitation à partager leurs questionnements sur le spectacle vivant « au féminin », ses archives et ses références. Femmes, attitudes performatives rassemble dix contributions, une « interview performative » de La Ribot et un entretien sur La Part du rite de Latifa Laâbissi et Isabelle Launay.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes féministes; arts; corps; cours; danse; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire de la danse; performance; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Radclyffe Hall: A life in the writing - Dellamora, Richard (University of Pennsylvania Press, 2011)
The Well of Loneliness is probably the most famous lesbian novel ever written, and certainly the most widely read. It contains no explicit sex scenes, yet in 1928, the year in which the novel was published, it was deemed obscene in a British court of law for its defense of sexual inversion and was forbidden for sale or import into England. Its author, Radclyffe Hall, was already well-known as a writer and West End celebrity, but the fame and notoriety of that one book has all but eclipsed a literary output of some half-dozen other novels and several volumes of poetry. In Radclyffe Hall: A Life in the Writing Richard Dellamora offers the first full look at the entire range of Hall's published and unpublished works of fiction, poetry, and autobiography and reads through them to demonstrate how she continually played with the details of her own life to help fashion her own identity as well as to bring into existence a public lesbian culture. Along the way, Dellamora revises many of the truisms about Hall that had their origins in the memoirs of her long-term partner, Una Troubridge, and that have found an afterlife in the writings of Hall's biographers. In detailing Hall's explorations of the self, Dellamora is the first seriously to consider their contexts in Freudian psychoanalysis as understood in England in the 1920s. As important, he uncovers Hall's involvement with other modes of speculative psychology, including Spiritualism, Theosophy, and an eclectic brand of Christian and Buddhist mysticism. Dellamora's Hall is a woman of complex accommodations, able to reconcile her marriage to Troubridge with her passionate affairs with other women, and her experimental approach to gender and sexuality with her conservative politics and Catholicism. She is, above all, a thinker continually inventive about the connections between selfhood and desire, a figure who has much to contribute to our own efforts to understand transgendered and transsexual existence today.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; discipline; europe; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; royaume-uni; régions géographiques; thématiques; études littéraires

Les femmes dans la Russie des Révolutions, 1861-1926 - Alpern Engel, Barbara (Nouvelle encyclopédie politique et historique des femmes, 2010)
Keywords: 1800-1899; 1860-1869; 1870-1879; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1990-1999; approches et analyses; cours; discipline; europe; his4330; histoire; histoire des femmes*; premier cycle; périodes historiques; rapports sociaux de sexe; russie; régions géographiques; sciences humaines